Artificial Intelligence Concepts, Methodologies, and Applications - Gajendra Kumar Ahirwar,; Suryabhan Pratap Singh,; K. Kanimozhi, (AG Volumes, 2022)
With the emerging role of data as business capital, businesses are realizing what digital entrepreneurs as well as disruptors already know: Data is a powerful tool for recognizing patterns, making choices, and taking action before competition. The changing position of the data in the value chain is pushing firms to aggressively explore better methods to create value from this new capital. This paper reviews the recent developments in the field of data management tools and technologies and also the use of Artificial Intelligence, Machine learning as well as deep learning technologies for data management. At the same time it also covers the challenges of the present day data management systems and their applications in various fields.